Death, Hair and Memory: Cremation’s Heterogeneity in Early Anglo-Saxon England - Williams, Howard (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2015)
This article reconsiders and extends the interpretation of the heterogeneity of early Anglo-Saxon (c. AD 425/50–570) cremation practices and their mnemonic and ideological significance. Cremation burials frequently contain grooming implements (combs, tweezers, razors and shears), often unburnt and sometimes fragmented. The addition of these items to graves can be explained as a strategy of ‘catalytic commemoration’ which assisted in choreographing the transformation and selective remembering and forgetting of the dead by the survivors. This article explores new evidence to reveal the varied character and fluctuating intensity of these practices among cremating communities across southern and eastern England during the fifth and sixth centuries AD. The evidence suggests new insights into how and why cremation was selected as an ideology of transformation linking the living and the dead.
Śmierć, włosy i pamięć: Różnorodność kremacji we wczesno-anglosaskiej Anglii
Keywords: Anglo-Saxon; combs; cremation; grooming implements; memory